ISPC Commentary on the Proposal for CRP3.7 - May 2011 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2011)
ISPC Commentary on the proposal for CRP 3.7: More meat, milk and fish by and for the poor (version of March 2011).